PENGARUH DIAGRAM BEBAS BENDA DALAM STRATEGI PENYELESAIAN SOAL SECARA SISTEMATIS (PS3) UNTUK MATERI DINAMIKA PARTIKEL TERHADAP HASIL BELAJAR SISWA KELAS X SMAN 1 BATUSANGKAR - SILVI DWI MAYORA; AMALI PUTRA; HIDAYATI HIDAYATI (Universitas Negeri Padang, 2018)
Forces is a part of vector mechanics. Students’ ability in completing the physics’ questions related to force and motion in general is still low. This research aims to know the influence of student worksheet as a systematic approach to problem solving toward students’ achievement. This research is a Pra-Experimental Design with One-Group Pretest Posttest that engages one class from grade X at SMAN 1 Batusangkar. The research data includes knowledge competence taken by using pretest and posttest, and students’ outcomes when the teaching was running were taken by using student worksheet. The analyzing data is using N-gain test to see the increasing of students’ outcomes in the teaching learning process, and using the relationship of pretest variable (X) and posttest variable (Y) test to see how big its influence toward students outcomes. From the data analysis can be concluded the two outcomes of the research data. The first one is the comparison between the students’ pretest subjection mean with the student worksheetsubjection mean and the posttest subjection mean which have the increasing and decreasing in the teaching learning process. The comparison of the highest subjection mean from the outcome of N-Gain test is the comparison between the subjection of pretest and the subjection of posttest which is 0,58. The second one is the outcome of the relationship between pretest score (X) and posttest score (Y) is 20,43%. It shows that the use of student worksheet in systematic approach to problem solving gives influence toward students’ outcome as big as 20,43%.